SELF-TALK DAN WAKTU REAKSI - Megantara, Surya Medal (STKIP Pasundan, 2018)
The purpose of this study is to determine the extent of the effect that self-talk has on the reaction time. In this study using the same research method with research methods conducted by tod et.al (2009). the population is all students of Level 3 PJKR Study Program. The sampling technique used is random sampling. Test results on these tests indicate that the significance level is 0. <0.05. Thus, ho is rejected and ha is accepted. In other words, there is an effect of self-talk on reaction time.